Collected essays - O'Doherty, Brian 1928-2022 (University of California Press, 2018)
"This long-awaited volume brings together much of Brian O'Doherty's most eloquent and influential writing, including essays on major figures such as Edward Hopper, Mark Rothko, and Andy Warhol and a substantial follow-up to his iconic Inside the White Cube. New pieces specifically authored for this collection include a meditation on O'Doherty's various alternate personae...most notably Patrick Ireland...and a reflection on his seminal "Highway to Las Vegas" from 1972, penned after a return visit in 2012. The beautifully written texts, many of which have been unavailable in print, are complemented by forty-five color illustrations that present artwork discussed in the essays as well as documentary photographs of O'Doherty and other major art world figures. Adventurous, original, and essentially O'Doherty, this book is an insightful contribution to the fields of writing, art history, and culture writ large"...Provided by publisher